Religious Movements in Contemporary America - Leone, Mark P.; Zaretsky, Irving I. (Book collections on Project MUSE., 1974)
Contemporary religious movements in America vary greatly in their organization, goals, methods, and membership. Reflecting the striking diversity of the current religious movement, the papers in this volume consider three categories of religious movements: native American churches, recently founded religious groups, and syncretistic groups based on imported cults. The general aim is to understand the varieties of human behavior within these institutions and to point out their relationship to society in the United States.Originally published in 1975.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.